Comparison of capacity design modes and operation strategies and calculation of thermodynamic boundaries of energy-saving for CCHP systems in different energy supply scenarios. (15th May 2019) - Feng, Lejun; Dai, Xiaoye; Mo, Junrong; Shi, Lin
Highlights: 21 system configurations were investigated for three energy supply scenarios. Six dimensionless energy matching parameters and three matching maps were proposed. Mathematical relationship between the matching parameters and ESR was established. Values of ESR were compared for different capacity design method and strategy. A thermodynamic boundary map of ESR was drawn and a survey in China was conducted. Abstract: In this research, 21 combined cooling, heating, and power (CCHP) system configurations that are based on gas engine (GE), gas turbine (GT), and microturbine (MGT) are investigated for three different energy supply scenarios: electricity & cooling, electricity & heating, and electricity & cooling & heating. Moreover, six dimensionless energy matching parameters are proposed to quantitatively measure the disparity of load demands. Thereafter, three matching maps for the GE/GT/MGT-based configurations are drawn to acquire direct insight on the energy matching performance between CCHP systems and users. Concurrently, the mathematical relationship between the matching parameters and energy-saving rate (ESR) is established. Moreover, the ESR values of different capacity design methods and operation strategies for the three energy supply scenarios are discussed and compared. The results show that the maximum ESR value is reached when the energy supply and demand achieved the ideal matching. The following electric load strategy (FEL) and the priority-to-providing-electricity capacity design method (PPE) are the better choices for most situations in terms of system design and operation control, respectively. Moreover, a thermodynamic boundary map of the ESR was drawn to intuitively understand the configurations of energy demands from the most suitable CCHP users as well as the boundaries of ESR for different energy supply scenarios. Finally, the survey results of the indigenous CCHP systems that had been conducted to gain insight on the development of these systems in China are presented in this paper.